Fattah, Irfan Abdul Hamid. “Freedom in Islamic Theological and Philosophical Thought,” Year 8, Issues 31-32 (Winter 1424 AH/ 2003 CE), Pp. 51-90. - فتّاح, عرفان عبد الحميد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2003)
Irfan Fattah’s study provides a view and historical survey of the concept of freedom in the classical and modern Western tradition and offers some methodological and critical observations on the concept of freedom in both Islamic and Western thought. It discusses the ta’ṣīl (foundation) of freedom of thought in Islam through a Qur’anic frame of reference and offers a historical presentation of the concept and view of freedom in Western tradition and its association with law, divine will, and with the political system and the state. It then addresses the critique of the concept of freedom of thought in Islam and presents some methodological observations. It concludes with a legal frame of reference for freedom of opinion in Islam from the precept of freedom of belief (i.e., from the Qur’anic statement that “There is no compulsion in religion”) and from the Sharīʿah objectives of preserving life (nafs) and intellect (ʿaql).